Highly acid-durable carbon coated Co3O4 nanoarrays as efficient oxygen evolution electrocatalysts - Yang, Xiulin; Li, Henan; Lu, Ang-Yu; Min, Shixiong; Idriss, Zacharie; Hedhili, Mohamed Nejib; Huang, Kuo-Wei; Idriss, Hicham; Li, Lain-Jong (Nano energy, 2016)
Most oxygen evolution reaction (OER) electrocatalysts are not stable in corrosive acids. Even the expensive RuO2 or IrO2, the most acid-resistant oxides, can be dissolved at an oxidative potential. Herein, we realize that the failures of OER catalysts are mostly caused by the weak interface between catalysts and the substrates. Hence, the study of the interface structure between catalysts and substrates is critical. In this work, we observe that the cheap OER catalysts Co3O4 can be more durable than the state-of-the-art RuO2 if the interface quality is good enough. The Co3O4 nanosheets deposited on carbon paper (Co3O4/CP) is prepared by electroplating of Co-species and followed by a two-step calcination process. The 1st step occurs in vacuum in order to maintain the surface integrity of the carbon paper and converts Co-species to Co(II)O. The 2nd step is a calcination in ambient conditions which enables the complete transformation of Co(II)O to Co3O4 without degrading the mechanical strength of the Co3O4-CP interface. Equally important, an in situ formation of a layer of amorphous carbon on top of Co3O4 further enhances the OER catalyst stability. Therefore, these key advances make the Co3O4 catalyst highly active toward the OER in 0.5M H2SO4 with a small overpotential (370mV), to reach 10mA/cm2. The observed long lifetime for 86.8h at a constant current density of 100mA/cm2, is among the best of the reported in literature so far, even longer than the state-of-art RuO2 on CP. Overall, our study provides a new insight and methodology for the construction of a high-performance and high stability OER electrocatalysts in corrosive acidic environments. Carbon coated Co3O4 array on carbon fiber paper (Co3O4@C/CP) are developed by electroplating methods combined two-step calcined treatments. The prepared catalysts reveal highly efficient oxygen evolution reaction in 0.5M H2SO4 with a small overpotential (370mV) to reach 10mA/cm2, and long-time stability at 100mA/cm2 for 86.8h. The excellent performance is proved to be related with the carbon layer protection and the interface force between the catalysts and the substrate. [Display omitted] •Carbon decorated Co3O4 arrays on carbon paper (Co3O4@C/CP) is designed.•An electroplating strategy combining unique two-step thermal-treatments is developed.•The Co3O4@C/CP exhibits longer stability and lower overpotential for acid-OER.•The effects of carbon layer protection and interfacial force of catalyst/substrate is discussed.